2013
DOI: 10.1093/jac/dkt282
|View full text |Cite
|
Sign up to set email alerts
|

In vitro activity of miltefosine as a single agent and in combination with voriconazole or posaconazole against uncommon filamentous fungal pathogens

Abstract: Miltefosine demonstrated synergy in 8/20 (40%) and 4/20 (20%) instances when combined with posaconazole and voriconazole, respectively. Synergy was most often observed against F. oxysporum and the mucormycetes. Study of miltefosine/azole combinations as a novel antifungal approach is indicated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
51
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(57 citation statements)
references
References 18 publications
4
51
1
Order By: Relevance
“…Recently, some reports have attributed the development of resistance to miltefosine during the treatment of visceral leishmaniasis to the overexpression of an ABC transporter (Leishmania tropica MDR1 [LtrMDR1]) and to changes in membrane sterol composition (25,26). The broad-spectrum antifungal activity of miltefosine has been demonstrated in vitro against planktonic cells of several medically important fungi, including dermatophytes, Candida sp., Cryptococcus sp., Aspergillus sp., Fusarium sp., Scedosporium sp., Histoplasma capsulatum, Rhizopus sp., and Sporothrix schenckii (27)(28)(29)(30)(31)(32), and no reports about resistance development have been made so far.…”
mentioning
confidence: 99%
“…Recently, some reports have attributed the development of resistance to miltefosine during the treatment of visceral leishmaniasis to the overexpression of an ABC transporter (Leishmania tropica MDR1 [LtrMDR1]) and to changes in membrane sterol composition (25,26). The broad-spectrum antifungal activity of miltefosine has been demonstrated in vitro against planktonic cells of several medically important fungi, including dermatophytes, Candida sp., Cryptococcus sp., Aspergillus sp., Fusarium sp., Scedosporium sp., Histoplasma capsulatum, Rhizopus sp., and Sporothrix schenckii (27)(28)(29)(30)(31)(32), and no reports about resistance development have been made so far.…”
mentioning
confidence: 99%
“…In 2006, Widmer et al used a 50% inhibition endpoint (9), while more recently, other authors chose a 100% inhibition endpoint (17). For our study, we determined interactions using both of these endpoints.…”
mentioning
confidence: 99%
“…Recently, Biswas et al reported an in vitro synergistic effect for miltefosine in combination with azoles against some Fusarium or Scedosporium isolates as well as several mucormycete strains but decided not to test the combinations against azole-susceptible strains (17). However, even when a strain is susceptible to both drugs independently, a combination may still be useful to potentially clear the pathogen more quickly and stave off the emergence of resistance.…”
mentioning
confidence: 99%
“…describe the successful treatment of S. prolificans osteomyelitis in an immunocompetent child with miltefosine, terbinafine and voriconazole therapy . Interestingly, a recent study demonstrated in vitro synergy of miltefosine, voriconazole and posaconazole against S. prolificans …”
Section: Discussionmentioning
confidence: 99%